Revision of the Palaearctic genus Gonaporus Ashmead, 1902 of spider wasps (Hymenoptera: Pompilidae) - Zonstein, Irina; Wahis, Raymond (Zootaxa, 2015)
Twelve species (including six new ones) of the spider wasp genus Gonaporus Ashmead, 1902 are revised. The composition of the genus is discussed. Six new species of Gonaporus are described: G. simulator Wahis & I. Zonstein, sp. nov. (♀ ♂, Egypt, Saudi Arabia, United Arab Emirates, Mauritania), G. emiratus I. Zonstein & Wahis, sp. nov. (♀ ♂, United Arab Emirates), G. jaziratensis Wahis & I. Zonstein, sp. nov. (♂, United Arab Emirates), G. mirabilis I. Zonstein & Wahis, sp. nov. (♀ ♂, United Arab Emirates, Pakistan), G. setitarsus I. Zonstein & Wahis, sp. nov. (♀ ♂, Pakistan), and G. spinosissimus Wahis & I. Zonstein, sp. nov. (♀ ♂, Oman). A new synonymy is proposed for G. ecbatanus Wolf, 1990 = G. flamingo S. Zonstein, 2001, syn. nov. Gonaporus israelicus (Wolf, 1990), comb. nov. is transferred from Micraporus Priesner, 1955. An emended diagnosis to genus and a key to species are provided. The Gonaporus species inhabit open arid sandy biotopes of the Mediterranean Region, Africa, Near East and Central Asia. The subgenus Stigmaporus S. Zonstein, 2001 is elevated to full generic rank, stat. nov. A new combination is proposed for S. centralasiaticus (Wolf, 1990), comb. nov., S. lystracantha (Wolf, 1988), comb. nov. and S. wolfi (S. Zonstein, 2001), comb. nov. (all are from genus Gonaporus).